Vaccination et vaccins anti COVID-19 - MABUNGU NDOMBE, Jonathan (My University, 2021)
Vaccination is one of the main means to fight infectious diseases and it is nowadays a real public health issue since it saves millions of lives around the world. It plays a major role in modern medicine, because thanks to its mallpox has been eradicated and some any other epidemics have been broughtunder control. Currently, the whole world is facing coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The death rate has prompted scientists to develop safe and effective vaccines to prevent the spread of the disease. Vaccines are the main intervention strategy in controlling the transmission of coronaviruses.In this context, various strategies have been developed for the manufacture of vaccines. Following the discovery of the Spike protein, several types of COVID-19 vaccines have developed such as : inactivated vaccines, nucleicacid (mRNA) vaccines, adenovirus vaccines, vector vaccines and recombinant subunit vaccines. So many other strategies are underdevelopment. In fact, more than 200 candidates vaccines are beingdeveloped, including more than 60 in the clinical trial phase.
Keywords: Keywords : vaccination, vaccine, SARS-Cov-2, Spike protein